OGC Consensus: How Successful Standards Are Made - Carl Reed; Kurt Buehler; Lance McKee (ISPRS International Journal of Geo-Information, 2015)
This paper describes the history, background, and current status of the Open Geospatial Consortium (OGC) standards development consensus process. The roots of the formation of the OGC lie in the early 1990s when a very strong market requirement for exchanging GIS data content was clearly stated. At that time, each GIS vendor had their own formats for publishing and/or exchanging their GIS data. There was no mechanism or organization that provided a forum for the GIS vendors and GIS data users to collaborate and agree on how to share GIS data. That requirement, along with the vision of a few individuals, led to the formation of the OGC. This paper describes the early development of the consensus process in the OGC, how this process has evolved over time, why consensus is so important for defining open standards that are implemented in the marketplace, and the future of the OGC consensus process.